Predictors of cardiovascular events after one year of molecular screening for Familial hypercholesterolemia. (July 2016) - Silva, Pãmela R.S.; Jannes, Cinthia E.; Marsiglia, Julia D.C.; Krieger, Jose E.; Santos, Raul D.; Pereira, Alexandre C.
Abstract: Background and aims: This study reports the first year follow-up of individuals enrolled in Brazil's genetic cascade screening program for Familial Hypercholesterolemia (FH), Hipercol Brasil. Predictors for the occurrence of cardiovascular (CV) events in individuals screened for FH were studied. Methods : This is an open prospective cohort of individuals who were included in a cascade genetic screening program for FH. The first prospective follow-up was carried out one year after patients received their genetic test result. Individuals included in this study were index cases (probands) and relatives with identified (M +) or not genetic mutations (M −). Logistic regression analysis was performed to determine predictive variables for the occurrence of CV events censored at one-year of follow-up. Results: A total of 818 subjects were included, 47 first CV events were ascertained, with 14 (29.7%) being fatal. For index cases, the only factor independently associated with increased risk of CV events was the presence of corneal arcus (OR: 9.39; 95% CI: 2.46–35.82). There was an inverse association of CV events with higher HDL-cholesterol levels (OR: 0.95; 95% CI: 0.90–0.99). For M+ relatives, risk factors associated with increased CV events risk were diabetes mellitus (OR: 7.97; 95% CI: 2.07–30.66) and tobacco consumption (OR: 3.70; 95% CI: 1.09–12.50). Conclusions: A high one-year incidence of CV events was found in this cascade-screening cohort. Predictors of events differed between index cases and relatives and can be useful for the development of preventive efforts in this highly susceptible group of individuals. Highlights: A high one-year incidence of CV events was found in this cascade screening cohort. Predictors of CV events are dependent on the result of the screening program. Longitudinal study in both probands and family members.